Temporal Trends of Out-of-Hospital Cardiac Arrests Without Resuscitation Attempt by Emergency Medical Services. Issue 3 (17th March 2021) - Waldmann, Victor; Karam, Nicole; Gaye, Bamba; Bougouin, Wulfran; Dumas, Florence; Sharifzadehgan, Ardalan; Narayanan, Kumar; Kassim, Haoiinda; Beganton, Frankie; Jost, Daniel; Lamhaut, Lionel; Loeb, Thomas; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Significant improvements in survival from out-of-hospital cardiac arrest (OHCA) have been reported; however, these are based only on data from OHCA in whom resuscitation is initiated by emergency medical services (EMS). We aimed to assess the characteristics and temporal trends of OHCA without resuscitation attempt by EMS. Methods: Prospective population-based study between 2011 and 2016 in the Greater Paris area (6.7 million inhabitants). All cases of OHCA were included in collaboration with EMS units, 48 different hospitals, and forensic units. Results: Among 15 207 OHCA (mean age 70.7±16.9 years, 61.6% male), 5486 (36.1%) had no resuscitation attempt by EMS. Factors that were independently associated with increase in likelihood of no resuscitation attempt included: age of patients (odds ratio, 1.06 per year [95% CI, 1.05–1.06], P <0.001), female sex (odds ratio, 1.21 [95% CI, 1.10–1.32], P =0.002), OHCA at home location (odds ratio, 3.38 [95%CI, 2.86–4.01], P <0.001), and absence of bystander (odds ratio, 1.94 [95% CI, 1.74–2.16], P <0.001). Overall, the annual number of OHCA increased by 9.1% (from 2923 to 3189, P =0.028). This increase was related to an increase of the annual number of OHCA without resuscitation attempt by EMS by 26.3% (from 993 to 1253, P =0.012), while the annual number of OHCA with resuscitation attempt by EMS did not significantly change (from 1930 to 1936, P =0.416). Considering only cases with resuscitation attempt, survival rate at hospital discharge increased (from 7.3% to 9.5%, P =0.02). However, when considering all OHCA, survival improvement did not reach statistical significance (from 4.8% to 5.7%, P =0.17). Conclusions: We demonstrated an increase of the total number of OHCA related to an increase of the number of OHCA without resuscitation attempt by EMS. This increasing proportion of OHCA without resuscitation attempt attenuates improvement in survival rates achieved in EMS-treated patients.